The diagnostic performance of 18F-DCFPyL PET in patients with suspected prostate cancer: A systemic review and meta-analysis - Pang, Wenyang; Cheng, Shulin; Du, Zhongbo; Du, Shuang (Frontiers in Oncology, 2023)
Introduction Our meta-analysis aimed to evaluate the diagnostic value of 18F-DCFPyL PSMA PET in patients with suspected prostate cancer. Methods We searched for articles that evaluate the diagnostic value of 18F-DCFPyL PSMA PET in patients with suspected prostate cancer in PubMed, Embase, Cochrane Library, and Web of Science until August 1, 2022. Using the QUADAS-2 instrument, two researchers independently assessed the effectiveness of the studies that were included. The four-grid table data were analyzed by Meta-disc1.4 and Stata 16.0 software. The heterogeneity of each study was tested. Results A total of 5 studies with 258 patients were included, and the pooled sensitivity and specificity of 18F-DCFPyL PSMA PET for primary prostate cancer were shown as follows: 0.92 (95% Confidence interval (CI): 0.85-0.96), 0.59 (95% CI: 0.08-0.96), respectively. 18F-DCFPyL PSMA PET was successful in detecting primary prostate cancer, with an AUC of 0.92 (95% CI: 0.89-0.94). Conclusions 18F-DCFPYL PSMA PET has a strong predictive value for primary prostate cancer and is an effective method for the noninvasive diagnosis of prostate cancer. More prospective articles were needed.